SOCIOLINGUISTIC CULTURE AS A METHODICAL PROBLEM - Roziqova Maysara Rustamovna; Khamroev Alijon Ruzikulovich (American Journals, 2024)
In this article, a wide analytical scientific article is written about the works on the topic of sociolinguistic culture in methodological quality.